Censorship detected in BD (Bangladesh) - Voidly (2026)
CRITICAL severity censorship detected in Bangladesh. Confidence: 81%. Data sourced from OONI.
Censorship Incident ID: BD-2026-0483
Keywords: censorship; BD; censorship; critical